2013
DOI: 10.1080/10409289.2013.736036
|View full text |Cite
|
Sign up to set email alerts
|

Rural Neighborhood Context, Child Care Quality, and Relationship to Early Language Development

Abstract: Research Findings Prior research with older urban children indicates that disadvantaged neighborhood context is associated with poorer early development, including poorer verbal ability, reading recognition, and achievement scores among children. Neighborhood disadvantage in rural communities and at younger age levels may also be related to development; however this relationship has received little examination. In this study we utilize data from the Family Life Project, a representative sample of babies born t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 80 publications
0
16
0
1
Order By: Relevance
“…They found that African American mothers experienced decreases in positive parenting practices as neighborhood conditions worsened. More recently, De Marco and Vernon-Feagans (2013) examined the relationship between neighborhood quality and language development in low-income White and African American families. They found that neighborhood safety predicted children's receptive language scores, with children from unsafe neighborhoods scoring lower than children from safer neighborhoods.…”
Section: Neighborhood and Demographic Characteristicsmentioning
confidence: 99%
“…They found that African American mothers experienced decreases in positive parenting practices as neighborhood conditions worsened. More recently, De Marco and Vernon-Feagans (2013) examined the relationship between neighborhood quality and language development in low-income White and African American families. They found that neighborhood safety predicted children's receptive language scores, with children from unsafe neighborhoods scoring lower than children from safer neighborhoods.…”
Section: Neighborhood and Demographic Characteristicsmentioning
confidence: 99%
“…[20] Studies have investigated various factors that can be linked with overcoming odds, such as moving to a more affluent area in early childhood,[21] living in an area with better access to green space,[22] safer community areas so the parents allow and encourage their children to be involved in outdoor physical activity,[23] and neighbourhood safety that enhances collective socialisation. [24,25] Though such evidence is fragmented, it indicates that improvement of the quality, facility and environment of the local area can help the children to build resilience and overcome adversity. Hence it is necessary to develop a holistic understanding of neighbourhoods and prioritise the various aspects of a local area which can help children and their parents to improve their life and overcome poverty.…”
Section: Introductionmentioning
confidence: 99%
“…Rural children are a largely understudied population in terms of language and literacy research (Vernon-Feagans, Gallagher, & Kainz, 2010), despite the fact that many children in rural areas enter school with delays in their language development (De Marco & Vernon-Feagans, 2013;Durham & Smith, 2006;Vogels & Bronneman-Helmers, 2003). The low language proficiency of young children in rural areas is often overshadowed by discussions of problems in urban areas (Atav & Spencer, 2002; De Marco & Vernon-Feagans, 2013;Sheridan, Koziol, Clarke, Rispoli, & Coutts, 2014). Although children in rural and urban areas both lag behind in language proficiency, their early home experiences, prior to their school career, are starkly different as a consequence of differences in the socio-economic and cultural environment (Kloprogge, 2003;Miller & Votruba-Drzal, 2013;Vernon-Feagans & Cox, 2013): Rural areas are sparsely populated, the work force is less educated and less differentiated, and employment opportunities, in particular for the more highly educated, are rare (Fish & Pinkerman, 2003;Hospers & Reverda, 2012;Melis, 2013;Thissen, Fortuijn, Strijker, & Haartsen, 2010;Vernon-Feagans, Garrett-Peters, De Marco, & Bratsch-Hines, 2012;Vernon-Feagans et al, 2008).…”
Section: Introductionmentioning
confidence: 99%